2014
DOI: 10.1038/sc.2014.62
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge translation and implementation in spinal cord injury: a systematic review

Abstract: ,5 and the SCIRE Research TeamObjective: To conduct a systematic review examining the effectiveness of knowledge translation (KT) interventions in changing clinical practice and patient outcomes. Methods: MEDLINE/PubMed, CINAHL, EMBASE and PsycINFO were searched for studies published from January 1980 to July 2012 that reported and evaluated an implemented KT intervention in spinal cord injury (SCI) care. We reviewed and summarized results from studies that documented the implemented KT intervention, its impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 34 publications
2
21
0
1
Order By: Relevance
“…However, the current study showed that some professionals experienced a lack of support from physiotherapists to embed physical activities into rehabilitation. In line with previous literature (27,39) we found that good communication and collaboration between members of the multidisciplinary team (e.g. sports therapists, physiotherapists, physicians) during implementation seems also essential for successful continuation.…”
Section: Discussionsupporting
confidence: 91%
“…However, the current study showed that some professionals experienced a lack of support from physiotherapists to embed physical activities into rehabilitation. In line with previous literature (27,39) we found that good communication and collaboration between members of the multidisciplinary team (e.g. sports therapists, physiotherapists, physicians) during implementation seems also essential for successful continuation.…”
Section: Discussionsupporting
confidence: 91%
“…For example, the challenges with the translation of cellular therapies for SCI was explored by an international group of stakeholders 27 and a systematic review of knowledge translation interventions identified barriers and facilitators to implementation. 28 Work has also been done to investigate the state of international collaborations in the area of science and provide recommendations for supporting collaboration. 29 , 30 From this survey and from the literature cited above, the theme of funding appears to be a common challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have also highlighted the variability that exists in the implementation and subsequent success of HAI prevention programs [ 16 , 37 ]. In SCI/D care delivery, a recent review has shown that knowledge translation and targeted implementation efforts may be particularly effective in changing SCI/D provider behavior and improving patient outcomes [ 38 ]. Our findings align with these studies and corroborate the need to increase provider awareness and knowledge around guidelines, ensure guidelines are tailored to the provider context, and enhance leadership support and provider education [ 16 , 22 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that the presence of local MPCs, whose role centers on overseeing compliance with the guidelines, was often helpful for implementation; however, a strong group of SCI/D providers could effectively support MRSA prevention activities. This is particularly important in the SCI/D setting given patient needs for interdisciplinary, integrated, and team-based care [ 38 ]. Further, future efforts should ensure that guideline dissemination reaches the full range of providers that care for patients with SCI/D and should focus on disseminating guidelines to providers with hands-on contact with patients in inpatient and other SCI/D care settings.…”
Section: Discussionmentioning
confidence: 99%